The physical state of senior pupils of gymnasium. - Mitzkan B.M; Potashnyouk I.V (Kharkov National Pedagogical University, 2011)
It is shown the morphological parameters of physical condition, level of chronic morbidity and physical preparedness of high school students to high schools and secondary schools. The experiment involved 283 high school students and 231 secondary school pupil. Functional status of the musculoskeletal system was evaluated by measuring muscle strength of hands, calculating the power index, respiratory system and cardiovascular system.